Art as a therapy to relieve symptoms of Attention Deficit/Hyperactivity Disorder (ADHD), in children (Al-Academy, 2022)
The aim of the present study is to evaluate the effectiveness of using Art as therapy to reduce the symptoms of Attention Deficit Hyper Activity Disorder (ADHD), in primary school children.A clinical approach was used to test the validity of the hypothesis of our study, conducted on two second and fourth-year primary school pupils from Algiers, aged 7 and 9 years respectively. In addition to the clinical observation and interview, we made use of the "Conners" scale for a (pre and post intervention) ADHD assessment, consisting of a combination of Art media in the form of mosaic works on purposely prepared panels. After 10 therapy sessions, results revealed the effectiveness of Art therapy in reducing ADHD in primary education children.Once the diagnosis of ADHD symptoms in the two study subjects, aged 7 and 9 years, was confirmed through the "Conners" ADHD assessment and by carrying out a clinical interview with the parents as well as an in-depth analysis of subjects’ clinical observation and interview, a treatment using Art as therapy was implemented and found to be very effective in reducing the symptoms of ADHD.In order to attract children’s attention, this type of therapy uses purposely designed graphics, since the assortment of colors made at their disposition prompted them to willingly engage in the activity and cooperate with the specialist implementing the treatment program.The child begins to ‘own’ the work of Art, absorbing himself with it until it was finished, all along stimulated by positive reinforcement. The piece of mosaic art has become the child’s focal point onto which he projects his frustrations and internal conflicts and discharges his emotions. Therefore, a child with ADHD can be helped settle down into calmer behaviours, by using Art media to decrease his hyperactivity. The more in-school training workshops and homework, the further this type of therapy would prove itself to be more effective compared to the other treatments used to treat this category of children.